Occupational and leisure-time physical activity and workload among construction workers – a randomized control study. (2nd January 2016) - Gram, B.; Westgate, K.; Karstad, K.; Holtermann, A.; Søgaard, K.; Brage, S.; Sjøgaard, G.
Abstract : Background : There is a lack of quantification of occupational physical activity (OPA) and leisure time physical activity (LTPA) among construction workers. Objectives : To describe physical activity energy expenditure (PAEE), physical workload, and the effect of a PA-intervention among construction workers. Methods : Sixty-seven Construction workers self-reported their physical activity (PA), had PA assessed directly (PAEE), and observed OPA using the tool "Posture, Activity, Tools and Handling." The PA-intervention (Intervention; n = 29, Controls; n = 24) included 3x20-min training/week for 12 weeks. Results : Baseline median OPA was 5036 MET-min/week and LTPA 2842 MET-min/week, p < 0.01. OPA directly recorded was (mean ± SE): 56.6 ± 3.2 J/kg/min and LTPA was: 35.7 ± 2.2 J/kg/min ( p < 0.001). Manual material handling was performed for ≥ 25% of working time by more than 50% of the participants. Post-intervention, the training group reduced overall PAEE compared to the control group but not specifically during work. Conclusions : OPA was within the maximum recommended level of 1/3 proposed in consensus guidelines but did not decrease with PA-intervention.